Ground Rules for Preschooler Exposure to the Digital Environment: A Review of Studies - Elena I.; Inna A.; Tatyana K.; Evgeniya V. (Psychology in Russia: State of Art, 2023)
Background. The range of digital technologies that children use from an early age has expanded significantly. Most studies demonstrate that preschoolers now spend substantially longer on digital devices and start using them at a younger age. Finding a solution for this challenge has research merits and relevance, as the data on benefits and harm of early preschoolers’ exposure to digital devices is contradictory. This poses a need to determine theoretically sound and practically validated criteria that could guide the duration and quality of children’s exposure to the digital environment. Objective. To review studies that contain recommendations on preschoolers’ exposure to the digital environment, namely, exposure limits and evidence to justify the limitation of preschoolers’ time on digital media. Design. The analysis starts by identifying theoretical foundations that researchers use in their studies of children’s behavior in the digital environment. This is followed by an overview of 40 studies that include research papers, official reports, and methodological recommendations made by healthcare and governmental organizations. Results. The review identified the following ground rules for children’s exposure to the digital environment: to provide for child’s interaction with a digital device, to use educational applications that will develop skills appropriate to the child’s age, to ensure mandatory supervision of children’s engagement by an adult who limits the exposure according to child’s age-related capabilities and creates conditions for active exploration of the real rather than a virtual world. Children’s cognitive development suffers the most from passive intake of digital content. Conclusion. The data herein can help to develop strategies to promote healthy and educational engagement of children with digital devices and media; however, the review highlights the insufficiency of psychophysiological research that would make it possible to practically validate the recommendations on the duration of preschoolers’ exposure to the digital environment.